2020
DOI: 10.14202/vetworld.2020.1209-1220
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization and phylogenetic study of Lakor goat from Southwest Maluku Regency based on mitochondrial COI gene

Abstract: Aim: This study is aimed at characterizing the genetic and phylogenetic structure of Lakor goats as indigenous livestock from the Southwest Maluku Regency based on mitochondrial COI gene sequences. Materials and Methods: The genomes of 103 follicle samples from Lakor goats, collected from Lakor Island, were analyzed. The polymerase chain reaction was used to amplify 1548 bp of the mitochondrial COI gene using two primer pairs (COIA and COIB). Following sequencing, genetic variation and phylogenetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
0
5
0
2
Order By: Relevance
“…Research by Volkandari et al (2019) and Rumanta et al (2020) reported that there is low genetic variation within the Lakor goat population after few generations of selection and domestication. This condition is due to improper breeding mechanisms and broodstock management.…”
Section: Reversementioning
confidence: 99%
See 2 more Smart Citations
“…Research by Volkandari et al (2019) and Rumanta et al (2020) reported that there is low genetic variation within the Lakor goat population after few generations of selection and domestication. This condition is due to improper breeding mechanisms and broodstock management.…”
Section: Reversementioning
confidence: 99%
“…Currently, the policy being socialized related to the use of genetic information from the GH gene to farmers on Lakor island is controlling breeding mechanisms and broodstock management may be done by selecting buck from neighboring villages and not from the same village as doe. Rumanta et al (2020), reported that on Lakor Island, respective villages have a permanent fence composed of rocks (local name is Lutur) to protect the mixing of livestock between villages. We assume that, in this way, the rate of genetic loss in the Lakor goat population can be reduced.…”
Section: Reversementioning
confidence: 99%
See 1 more Smart Citation
“…Data genetik dapat memberikan kontribusi penting dalam pemahaman konektivitas populasi, strategi konservasi dan pengelolaan, termasuk di dalamnya penentuan daerah konservasi (Díaz-Ferguson et al, 2010). Analisis kekerabatan, sejarah evolusi maupun dinamika evolusi dapat dipelajari melalui rekonstruksi filogenetik (Sohpal, 2013;Rumanta et al, 2020). Pendekatan filogenetik molekuler telah banyak dilakukan dalam mengidentifikasi spesies ikan (Jefri et al, 2015;Saleky et al, 2020;Dailami et al, 2021).…”
Section: Pendahuluanunclassified
“…Rekonstruksi pohon filogenetik Pendekatan filogenetik molekuler dapat digunakan untuk membedakan dan mengidentifikasi spesimen yang sulit diidentifikasi (Jefri et al, 2015). Rekonstruksi pohon filogenetik molekuler memanfaatkan data biomolekuler struktural atau fungsional yang dapat digunakan untuk konstruksi pohon filogenetik (Pardi et al, 2016;Rumanta et al, 2020 filogenetik dan keragaman genetik seluruh sampel yang dianalissi memiliki 1 haplotipe dengan jarak genetik 0,000 -0,0032 pada ikan nila sedangkan pada ikan mujair seluruh sampel memiliki jarak genetik 0,000. DNA barcode dapat digunakan dalam mengidentifikasi dan konfirmasi spesies dalam pengelolaan dan konservasi spesies.…”
Section: Jarak Genetikunclassified